PERCENTAGE UPTAKE OF HEAVY METALS OF DIFFERENT MACROPHYTES IN STAGNANT AND FLOWING TEXTILE EFFLUENT - A. Yasar; M. Khan; A. B. Tabinda; M. U. Hayyat; A. Zaheer (Journal of Animal and Plant Sciences, 2013)
Concentration of different heavy metals in various plant species was analyzed in two different drains having Stagnant and Flowing water. Pistia stratiotes Cu(0.33ppm), Pb (1.48 ppm), Typha angustifolia Cu (0.21ppm), Pb (1.58ppm), Eichornia crassipes Cr (0.24ppm), Pb (1.48ppm) and Phragmites karka Cu (0.20ppm) and Pb (1.37ppm) in Flowing water where as in Stagnant water metal concentration is Schenoplectus litoralis Cd (0.18ppm), Pb (3.19ppm ) and Dichanthium annulatum Cd (0.19 ppm), Pb (3.25ppm). Bioconcentration factor of certain heavy metals was also calculated and different plant species showed varied uptake at different metal concentrations in textile effluent. Bioconcentration factor of Pistia stratiotes for Cu and Ni was 140.72 and 377.36 at concentration in flowing textile effluent 0.23 ppm and 0.063ppm respectively. Eichornia crassipes showed maximum bio concentration factor for Cr 176.63 at 0.36 ppm concentration in flowing water. In Stagnant water Dichanthium annulatum and Schoenoplectus litoralis showed bioconcentration factor for Pb 264.23ppm and 259.23ppm respectively. Over all Pistia stratiotes appeared to be best the accumulator with high bioconcentration factor (>100) for different heavy metals.
Keywords: Phytoremediation; Aquatic macrophytes; Bioaccumulation; Heavy metals